PERBANDINGAN HASIL BELAJAR BIOLOGI SISWA ANTARA KELAS YANG MENERAPKAN PEMBELAJARAN TGT (TEAM GAMES TOURNAMENT) DENGAN KELAS YANG MENERAPKAN PEMBELAJARAN STAD (STUDENT TEAMS ACHIEVE- MENT DIVISION) MENGGUNAKAN HANDOUT - Jumiati, Jumiati; Lizawati, Lizawati (Universitas Lancang Kuning, 2014)
ABSTRACT: This research aimed to know the comparison of students’achievemeat in biology between class who apply TGT (tournament team games) with a class who apply STAD (student achievement division team) using handouts in the digestive system at VII grade studentsSMPN 19 Pekanbaru.This research was conducted in odd semester, October 2014.The design of the researchwasweak experiment, the static group pretes-posttest Design.The sample wasthe students gradeVIII1 and VIII2. With the member of each class was 35 students.Which taken by simple random sampling. Data were collected, through pretest, posttest, andteacher’s and students’activity sheets.Data were analysed by using independent t-test independent 2sample. The everage ofN-Gain in TGT class was 0.72 (high)and STAD class was 0.42 (middle). There fore, it cau be concluded that there was a differences on student’ learning achievement on class who apply TGT and STAD. Learning model TGT was better tobe used to impore student’s learning achieveman grade VIII SMP Negeri 19 Pekanbaru academic year 2014/2015.